Békét nem lelek… – Francesco Petrarca 104. szonettjének magyar fordításai - Képes, Julianna (Antikvitás & Reneszánsz, 2019)
In this paper, I focus on Petrarch’s Sonnet 104 (Pace non trovo, et non ho da far guerra) in the respective Hungarian translations of György Sárközi, Győző Csorba and György Somlyó. I provide a comparative analysis between the original and each of the above mentioned translations, as well as between the three Hungarian translations of the same piece of poetry, pointing out the adequate and less adequate solutions. Based on the conclusions of this comparative analysis, I conclude by offering my own translation of Petrarch' Sonnet 104, which avoids some of the pitfalls of the earlier translations.